Developing a measure to understand young children's Internet cognition and cyber-safety awareness: a pilot test. Issue 3 (2nd July 2016) - Edwards, Susan; Nolan, Andrea; Henderson, Michael; Skouteris, Helen; Mantilla, Ana; Lambert, Pamela; Bird, Jo
Abstract: Advancements in technology have increased preschool children's access to the Internet. Very little research has been conducted to identify pre-school-aged children's understandings of the Internet and ramifications of being 'online'. Without an understanding of children's thinking about the Internet, it is difficult to provide age- and pedagogically appropriate cyber-safety education. This study developed and pilot-tested an interview schedule that focuses on the Internet thinking and cyber-safety awareness of Australian children aged 4–5 years. The schedule is informed by sociocultural theory, cyber-safety education research and approaches for researching with young children. The schedule shows potential to elicit children's understandings of the Internet and cyber-safety awareness. Adjustments are required to allow more contextualised responses from children.